Apotheosis of the North : the Swedish appropriation of classical antiquity around the Baltic Sea and beyond (1650 to 1800) - Roling, Bernd; Schirg, Bernhard; Bauhaus, Stefan Heinrich (Transformationen der Antike, 2017)
Although Antiquity itself has been intensively researched, together with its reception, to date this has largely happened in a compartmentalized fashion. This series presents for the first time an interdisciplinary contextualization of the productive acquisitions and transformations of the arts and sciences of Antiquity in the slow process of the European societies constructing a scientific system and their own cultural identity, a process which started in the Middle Ages and has continued up to the Modern Age. The series is a product of work in the Collaborative Research Centre "Transformations of Antiquity" and the "August Boeckh Centre of Antiquity" at the Humboldt University of Berlin. Their individual projects examine transformational processes on three levels in particular - the constitutive function of Antiquity in the formation of the European knowledge society, the role of Antiquity in the genesis of modern cultural identities and self-constructions, and the forms of reception in art, literature, translation and media. * new transdisciplinary series * the editors are prominent professors from different disciplines at the Humboldt University of Berlin * strengthens de Gruyter's profile in Classical Studies, Medieval Studies, Intellectual History.